PROFESIONALISME SEBAGAI PEMODERASI PENGARUH KEMAMPUAN INVESTIGATIF PADA PEMBUKTIAN KECURANGAN OLEH AUDITOR BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN PROVINSI BALI - Dewi, Ni Wayan Puspita; Ramantha, I Wayan (E-Jurnal Akuntansi, 2016)
The purpose of this study was to determine the ability of returning Effect on Evidence Investigative Fraud By Auditor Financial and Development Supervisory Agency Bali Province. In addition, this study also aims to determine whether Professionalism will moderate influence on the ability Investigative Fraud Verification by the Auditor and Financial Supervisory Agency of Bali Provincial Development. The study was conducted in the Office of Financial and Development Supervisory Agency (BPKP) of Bali in 2016. The number of samples taken as many as 74 people auditor. The data collection is done by distributing questionnaires to the auditor. Data analysis technique used is simple regression analysis and test MRA (Moderating Regression Analysis). Based on the analysis, it is known that the ability of Investigative positive effect on Evidence Cheating By Auditor Financial and Development Supervisory Agency Bali Province. The study also found that professionalism is able to strengthen the influence of the Investigative Capability Verification Cheating By Auditor Financial Supervisory Agency of Bali Province.
Keywords: Professionalism, Investigative Capabilities, Evidence Cheating